Separation and deformation of red blood cells in PDMS microchannels - Rodrigues, Raquel Oliveira (2013)
Over the years, several experimental techniques were performed in in vitro environments, in an attempt to understand the flow behaviour of blood in microcirculation. Several of these studies were performed in glass capillaries, and have produced significant results with respect to rheological properties of blood [1, 2]. Another way to perform in vitro blood studies is to use microchannels fabricated by soft- lithography [3, 4] and xurography [5]. With these techniques several studies have focused in the formation of the cell-free layer (CFL) that is caused by the tendency of red blood cells (RBCs) to migrate toward the centre of the microchannel, in that the physical reason is known as the Fahraeus Lindqvist. The presence of this CFL at the regions adjacent to the wall is affected by the geometry of the microchannel [4] and the physiological conditions of the working fluid, such as the hematocrit (Hct) [6], and the RBC deformability [7]. The formation of CFL can be used for separation of diseased cells from healthy blood cells [8]. The aim of this paper is to show briefly the importance of the microfluidic devices to study several physiological phenomena that happens in vivo environments with special focus on the CFL behaviour and RBC deformability.